L Appel de la forêt - Jack London (Open Library, 1903)
A classic novel of adventure, drawn from London's own experiences as a Klondike adventurer, relating the story of a heroic dog, who, caught in the brutal life of the Alaska Gold Rush, ultimately faces a choice between living in man's world and returning to nature. Note.
Droits : Métadonnées bibliographiques et couverture issues d Open Library
Keywords: nature; aventure; Jack London; classique; Littérature